Implementasi Metode Clustering DBSCAN pada Proses Pengambilan Keputusan - Devi, Anindya Santika; Putra, I Ketut Gede Darma; Sukarsa, I Made (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.3 Desember 2015, 2015)
Spatial Data Clustering is one of the significant techniques in data mining which used to obtain information or knowledge in a large number of spatial data from various applications. One technique that being a pioneer in the development of spatial data clustering algorithm is DBSCAN. This study is focused on implementation of DBSCAN method in decision making process in order to help a company to decide its potential customer. The trial results in this study show that DBSCAN method has been successfully conduct clustering process to support decision making process in determination of potential customer by forming several number of clusters.